APPLICATION FOR VIBRATION DIAGNOSTICS - Stakhova, Anzhelika (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
This paper considers the issue of developing an application for vibration diagnostics of bearings of functional pairs of critical structures, this application should help in monitoring and diagnosing bearings, using vibration signals, without disassembling the functional unit itself. It is known that vibration diagnostics is effective and there is a tendency to reduce the cost of its implementation. Monitoring and diagnostics based on vibration parameters can be applied at any time, even after several years of equipment operation, when the costs of preventive maintenance and repair will exceed the economically justified value. Also, in the work, the basics of the subject area for the development of mobile applications are considered, and a review of existing solutions is made. Requirements for the application for performing vibration diagnostics are formulated. The architecture is designed and the data description for the application of vibration diagnostics is carried out.